Investments : Theoretical aspect (Eurasian Journal of History, Geography and Economics, 2023)
The role of investment in the service sector during the period of changes in the economy of Uzbekistan is analyzed. The components of investments are determined; its main features are formulated. Statistics for 2022 are shown . Information is shown to the issued decrees of the President of the Republic of Uzbekistan and adopted laws; revealed their relationship